2005
DOI: 10.1016/j.jad.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment disorder and the course of the suicidal process in adolescents

Abstract: Background: Adjustment disorders are often associated with suicidal behaviour but there is little information regarding the nature of the relationship and the effect of adjustment disorders on the suicidal process. The authors' goal was to investigate the association of adjustment disorders (with depressed mood) and suicide in adolescents by means of a psychological autopsy study. Method: Relatives and other informants of 19 suicide victims were interviewed by means of a semi-structured interview schedule. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 20 publications
5
31
0
4
Order By: Relevance
“…Stressful life events accounted for 14% of the deaths and 15% were classified as a result of experimentation, with half of these deaths due to using drugs or alcohol. In a psychological autopsy study of suicide deaths of 19 young people in Belgium [23], the authors identified a subset of young people who had no previous behavioral or emotional difficulties but who completed suicide following the development of an adjustment disorder [22]. A case-control psychological autopsy study by Shaffer et al [27] examined 120 consecutive suicides (mean age 16 years) in an ethnically diverse area of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful life events accounted for 14% of the deaths and 15% were classified as a result of experimentation, with half of these deaths due to using drugs or alcohol. In a psychological autopsy study of suicide deaths of 19 young people in Belgium [23], the authors identified a subset of young people who had no previous behavioral or emotional difficulties but who completed suicide following the development of an adjustment disorder [22]. A case-control psychological autopsy study by Shaffer et al [27] examined 120 consecutive suicides (mean age 16 years) in an ethnically diverse area of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…7 Suicidal behaviours occur earlier in the course of AD than in DE, 6 as does suicide. 8,9 All aspects of suicidality, including suicidal ideation, behaviour or death by suicide have been under researched in AD, instead focussing on DE and other mood disorders. 7 This neglect is surprising considering suicidality is commonly associated with AD in the emergency department (ED) 10 and among among those admitted for in-patient psychiatric treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, movement from a death wish through to a suicide attempt has been interpreted as a hierarchy of intent [2], and a number of authors have discussed this under the general concept of ''the suicidal process'' [3][4][5]-the term adopted here.…”
Section: Introductionmentioning
confidence: 99%